Septic Shock and Multi-Organ Dysfunction Syndrome in a Patient with Extensive Tophaceous Gout, Diagnostic and Management Challenges in South Papua: A Case Report - Chandra Kusuma, Hendrawan; Sri Rejeki, Ni Made Darma Parni; Sitorus, Pamela Yacinta (Masters Program in Public Health, Sebelas Maret University, 2025)
Introduction: Septic shock and multiple organ dysfunction syndrome (MODS) are interrelated medical conditions arising from the body's response to severe infection. Extensive tophaceous gout is recognized for its potential to worsen kidney failure, thereby negatively impacting the prognosis of patients suffering from septic shock and MODS. Case presentation: This case report describes a male patient in his 40s who presented to the emergency department in an unresponsive state and was diagnosed with septic shock, likely secondary to pneumonia, which progressed to MODS. The patient also had uncontrolled hyperuricemia, resulting in extensive tophaceous gout that may have contributed to renal failure. Despite receiving appropriate fluid resuscitation, vasopressors, and antibiotics, the patient succumbed to severe complications. Key challenges in managing this case included limited diagnostic resources, low health awareness, and unclear health insurance coverage, particularly in the context of medical care in South Papua, Indonesia. Results: The case illustrates the interplay between chronic gout and acute infection. Hyperuricemia may contribute to renal impairment, weaken immune defenses, and worsen outcomes in septic patients—challenges in health access, diagnostics, and patient awareness further complicated management. Conclusion: Our case report emphasizes the possible contribution of unmanaged gout to the deterioration of septic shock, leading to MODS.